Phylogeography of three Southern African endemic elephant-shrews and a supermatrix approach to the Macroscelidea - Smit, Hanneline Adri (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2008.